2018
DOI: 10.1016/j.cmi.2017.07.022
|View full text |Cite
|
Sign up to set email alerts
|

The impact of preoperative bacteriuria on the risk of periprosthetic joint infection after primary knee or hip replacement: a retrospective study with a 1-year follow up

Abstract: Objectives: Patients who undergo elective joint replacement are traditionally screened and treated for preoperative bacteriuria to prevent periprosthetic joint infection (PJI). More recently, this practice has been questioned. The purpose of this study was to determine whether preoperative bacteriuria is associated with an increased risk of PJI. Methods: Patients who had undergone a primary hip or knee replacement in a tertiary care hospital between September 2002 and December 2013 were identified from the hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
0
21
1
Order By: Relevance
“…These data suggest that searching and treating candidal intertrigo before hip surgery could be a simple, safe, and inexpensive measure to avoid CPJI. The approach to take in candiduria would be less clear-cut when there are no symptoms, as occurs with asymptomatic bacteriuria [21,22]. It has been reported that hematogenous seeding of a prosthetic joint is a common complication of Staphylococcus aureus bacteremia [23], but to our knowledge, the risk of developing CPJI after experiencing candidemia is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…These data suggest that searching and treating candidal intertrigo before hip surgery could be a simple, safe, and inexpensive measure to avoid CPJI. The approach to take in candiduria would be less clear-cut when there are no symptoms, as occurs with asymptomatic bacteriuria [21,22]. It has been reported that hematogenous seeding of a prosthetic joint is a common complication of Staphylococcus aureus bacteremia [23], but to our knowledge, the risk of developing CPJI after experiencing candidemia is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…No literature was found through manual search, duplicated articles were removed, and articles that did not meet the inclusion criteria also were removed. A total of articles were read in detail, were removed, and 9 were finally included [8][9][10][11][17][18][19][20][21]. There were 29844 cases of joint replacement and 2366 cases of asymptomatic bacteriuria, among which 6 were retrospective cohort studies, 1 was a prospective cohort study, and 2 were prospective randomized controlled studies, as shown in the literature screening process Figure 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The results showed that compared with the control group, patients with asymptomatic bacteriuria during the perioperative period of joint replacement were more likely to suffer from periprosthetic infection with a significant difference (OR=3.15, 95% CI: 1.23-8.02, P=0.02), as shown in Figure 2. After removing the article of Honkanen et al [9], heterogeneity decreased: I 2 =42%, P=0.12, there was moderate heterogeneity, which was demonstrated by the fixed effect model; the difference between the two groups was still significant (OR=3.81, 95% CI: 2.46-5.91, P < 0.000 01). See Figure…”
Section: Amentioning
confidence: 88%
See 2 more Smart Citations